Postgraduate Research Handbook (AACSB ; Association of MBAs, 2020)
The second edition of this best-selling book will be as lively and accessible as the first edition. As a book, it helps to keep students' momentum going, helps them enjoy the process of research and ultimately ensures they can produce a high quality dissertation or thesis. Advice, support and both active and reflective tasks take the students through the stages of research as well as encouraging them to consider social and cultural issues, such as working with their supervisor and other researchers. It is the ideal companion for postgraduate students studying for an MA, MPhil, EdD or PhD, and will be useful for those supervisors looking for extra support for their students.